Thrombin regulation of synaptic transmission and plasticity: implications for health and disease - Ben Shimon, Marina; Lenz, Maximilian; Ikenberg, Benno; Becker, Denise; Shavit Stein, Efrat; Chapman, Joab; Tanne, David; Pick, Chaim G.; Blatt, Ilan; Neufeld, Miri; Vlachos, Andreas; Maggio, Nicola (Frontiers in Cellular Neuroscience, 2015)
Thrombin, a serine protease involved in the blood coagulation cascade has been shown to affect neural function following blood-brain barrier breakdown. However, several lines of evidence exist that thrombin is also expressed in the brain under physiological conditions, suggesting an involvement of thrombin in the regulation of normal brain functions. Here, we review ours’ as well as others' recent work on the role of thrombin in synaptic transmission and plasticity through direct or indirect activation of Protease-Activated Receptor-1 (PAR1). These studies propose a novel role of thrombin in synaptic plasticity, both in physiology as well as in neurological diseases associated with increased brain thrombin/PAR1 levels.